2019
DOI: 10.20902/ijctr.2019.120315
|View full text |Cite
|
Sign up to set email alerts
|

Use of calcium phosphates to remove nickel, copper and cobalt ions from aqueous solutions

Abstract: This work concerns the use of amorphous tricalcium phosphate and apatitictricalcium phosphate to remove nickel, copper and cobalt ions from aqueous solutions. The amorphous or apatitic calcium phosphates were first exposed to separate solutions of Ni(II), Cu(II) or Co(II) salts for 48 hours at room temperature, then residual solids and solutions were separated and analysed. X-ray photoelectron spectroscopy, X-ray diffraction and infrared spectroscopy were applied to observe chemical and structure modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The equivalence between the proportions of copper ions removed from the solution and those of calcium ions released by the phosphates leads to predict a copper retention mechanism involving a simple exchange between these two ions. The involvement of such a mechanism has been clearly identified in the retention of nickel ions by amorphous and apatitic phosphates [10]. In this case, it has been shown that the exchange of nickel with calcium ions occurs without causing any change in the structures of the two phosphates.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The equivalence between the proportions of copper ions removed from the solution and those of calcium ions released by the phosphates leads to predict a copper retention mechanism involving a simple exchange between these two ions. The involvement of such a mechanism has been clearly identified in the retention of nickel ions by amorphous and apatitic phosphates [10]. In this case, it has been shown that the exchange of nickel with calcium ions occurs without causing any change in the structures of the two phosphates.…”
Section: Discussionmentioning
confidence: 92%
“…Subject to similar treatment, HA remains relatively intact. This contrast in reactivity between HA and tricalcium phosphates prompted interest in discovering how these phosphates might then be distinguished from HA when challenged for use in metal ion retention processes [10]. Experiments carried out with nickel, cobalt, and copper ions have unambiguously demonstrated the ability of amorphous and apatitic phosphates to remove variable but significant amounts of these metal ions from aqueous solutions [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations